Knowledge, awareness, and perception of contraception among senior pharmacy students in Malaysia: a pilot study - Elkalmi, Ramadan Mohamed Mahmod; Khan, Muhammad Umair; Ahmad, Akram; Srikanth, Akshaya B.; Ab Rahman, Norny Shafinaz; Jamshed, Shazia Qasim; Awadh, Ammar Ihsan Jawad; Ab. Hadi, Hazrina (Medknow, 2015)
Objective: This study aimed to assess the knowledge, awareness, and perception of contraception among senior pharmacy students of a public sector university in Malaysia. Methods: A cross‑sectional, questionnaire‑based study was conducted among senior pharmacy students. The pretested questionnaire was used to collect data from the participants over the period of 1‑month. The questionnaire was divided into four sections, for gathering the information about students’ demographic data, and their knowledge, attitudes, and perception toward contraception. Data were statistically analyzed using SPSS version 20. Findings: The response rate was 68.6%. The results showed that the contraceptive knowledge was comparatively higher in year four students (P < 0.001), married respondents (P < 0.001) and those taking elective courses (P = 0.022) as compared to their respective counterparts. Majority of the students were well aware and had a positive perception about contraception. Conclusion: Overall findings reflect that the majority of the students had good knowledge, perception, and awareness about contraception. The study recommends future studies to be conducted covering different pharmacy schools across the country to further establish the results.